2022
DOI: 10.1177/1759720x221124545
|View full text |Cite
|
Sign up to set email alerts
|

Potential complementary and/or synergistic effects of curcumin and boswellic acids for management of osteoarthritis

Abstract: For several thousand years (~4000) Boswellia serrata and Curcuma longa have been used in Aryuvedic medicine for treatment of various illnesses, including asthma, peptic ulcers, and rheumatoid arthritis, all of which are mediated through pathways associated with inflammation and pain. Although the in vivo pharmacology of both these natural ingredients is difficult to study because of poor bioavailability, in vitro data suggest that both influence gene expression mediated through nuclear factor kappa B (NF-κB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…The observations from the present study establish and validate the anti-OA efficacy and early onset of pain relief, improvements in musculoskeletal functions, and joint mobility in the male and female participants. Another objective of this study was to evaluate the clinical efficacy of a widely investigated combination of C. longa rhizome and B. serrata gum resin extracts ( 9 ). A meta-analysis performed on a series of preclinical and clinical studies supports that the blends of these two anti-inflammatory botanical extracts provide potential benefits in mitigating joint pain and improving musculoskeletal functions in OA subjects ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observations from the present study establish and validate the anti-OA efficacy and early onset of pain relief, improvements in musculoskeletal functions, and joint mobility in the male and female participants. Another objective of this study was to evaluate the clinical efficacy of a widely investigated combination of C. longa rhizome and B. serrata gum resin extracts ( 9 ). A meta-analysis performed on a series of preclinical and clinical studies supports that the blends of these two anti-inflammatory botanical extracts provide potential benefits in mitigating joint pain and improving musculoskeletal functions in OA subjects ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medicinal plants have been explored adequately to overcome such adverse events ( 7 ). Previous studies have shown that the synergistic activity of curcumin and boswellic acids reduced the dosage and intake frequency of acetaminophen and NSAIDs ( 8 , 9 ). Despite advanced treatment options, no substantial therapy can curb the disease progression or avert structural damage ( 10 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Boswellia is very effective in reducing pain, providing a synergistic effect. Combining Boswellia with other herbal anti-inflammatories may be even more beneficial [64,65]. It has been shown that the combination of curcumin with boswellic acid is effective in reducing pain-related symptoms in patients with OA [65].…”
Section: Salai Guggul (B Serrata)mentioning
confidence: 99%
“…Several studies suggest a mix of curcumin with boswellic acid [64,65]. Both substances influence gene expression and modify the NFκB pathway.…”
Section: Role Of Curcumin In the Prevention Of Arthritismentioning
confidence: 99%